Song Text Composition in Pinloin among the Indigenous Jahai of Peninsular Malaysia: A Local Postmodernist Approach? - Chan, Clare, Suet Ching (Malaysian Journal of Music, 2016)
The Jahai are one among 18 indigenous Orang Asli groups in Peninsular Malaysia. They perform the traditional pinloin, a song and dance genre, during the pano ceremony (séances) and tree and fertility rituals. The song text and music of pinloin is taught to the Jahai halaq (shaman) by their chenoi (spirit guide) through dreams. Pinloin song text manifests the flora and fauna of the rainforest of Malaysia as depicted by the chenoi. Today (2016), the function of pinloin as a ritual enactment has shifted to a form of entertainment or cultural experience for tourists, visitors and visiting dignitaries. This change has resulted in a disruption in the transmission of the traditional pinloin song text. In this article, I argue that there is an increase in the use of the pastiche approach such as random sharing of fragments of song text, sporadic unfolding of narratives and little connection between the title and song text in pinloin song text compositions due to the influence of the ‘tourist gaze’. I support this argument by comparing Jahai song text form and composition technique in the early 20th century, late 20th century and early 21st century.